Effects of a loaded change of direction training program on physical performance in U-19 elite soccer players - Martín, V.; Ben Brahim, M.; Hernaiz-Sánchez, A.; Yassin, H.; Sal-de-Rellán, A. (PLOS ONE, 2025)
Changes of direction are one of the most repeated actions during football matches, which is why the inclusion of these actions in the training of the football player must be a fundamental aspect. The aim of this study was to assess the effects of 6-week a loaded change of direction (COD) movements training on speed, jump, COD speed, and repeated sprint ability (RSA) in soccer players. Twenty-eight male soccer players (age: 19.12 ± 0.75 years; height: 1.75 ± 0.06 m; body mass: 72.78 ± 4.87 kg; systematic practice: 8.62 ± 1.33 years) were randomly assigned to an experimental group (EG, n = 14) or a control group (CG, n = 14). The research was conducted during a training camp. During the intervention period, the EG performed two weekly sessions of loaded change of direction training, while the CG performed FIFA 11 prevention program. EG significantly improved the performance of 5-m, CMJ, SJ, Illinois and the percentage of decrement (%Dec and %Dec-COD). However, CG only showed significant improvements in CMJ and SJ. Between-groups analysis revealed differences in favor of the EG in 5-m, CMJ, SJ. The main results show that the effect of loaded COD movements training using a weighted vest on the physical performance of soccer players is significantly greater compared to the FIFA 11 prevention program. This study shows that including an additional load in COD exercises is a good method to increase performance on key variables for soccer players.